“What is ‘Privilege’?”: A Counseling Curriculum Tool to Operationalize American Counseling Association’s Multicultural and Social Justice Counseling Competency Framework for Counselor Trainees - Sheri Castro-Atwater (COUNS-EDU: The International Journal of Counseling and Education)
This article describes the rationale and design of a “What is Privilege?” tool designed to help counselor trainees become aware of the privileges they hold and the role these may play in their personal and professional lives. This tool serves as a critical self-awareness assessment instrument that can be used to operationalize the American Counseling Association’s Multicultural and Social Justice Counseling Competency (MSJCC) framework within counselor education programs, particularly the domain of “counselor self-awareness”. It also serves as a critical training tool that defines the term of “privilege” within three pillars: powers, resources and freedoms, using probing prompts to identify how counselor trainees have experienced these, and/or from which they have benefitted.